2017
DOI: 10.1016/j.cej.2017.07.045
|View full text |Cite
|
Sign up to set email alerts
|

Polyamide-6 for the removal and recovery of the estrogenic endocrine disruptors estrone, 17β-estradiol, 17α-ethinylestradiol and the oxidation product 2-hydroxyestradiol in water

Abstract: The removal and recovery of highly potent endocrine disrupting chemicals (EDCs) estrone (E1), 17β-estradiol (E2) and 17α-ethinylestradiol (EE2) and the oxidation product 2hydroxyestradiol (2OHE2) in water was achieved on Polyamide 6 (PA6) particles. Hydrogen bonding was the main mechanism driving the adsorption of these EDCs on PA6 at pHs lower than the EDCs pKas (~10.5) and their adsorption was not affected by the water matrix nor by solute-solute interaction. The adsorption isotherms were linear and the valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 42 publications
(49 reference statements)
0
11
0
Order By: Relevance
“…Earlier study showed that sorption of PFOS on PE, PS, and PVC decreased with increasing pH (Wang et al, 2015). Tizaoui et al (2017) also reported that increasing pH of reaction system can reduce endocrine disrupting chemicals (EDCs) adsorption on PA significantly. On the other hand, ionic strength, to a certain extent, could affect the electrostatic interactions since the electrolytes can compete with adsorbate for electrostatic sites (Shen and Gondal, 2017).…”
Section: Freshwater and Seawater Systemsmentioning
confidence: 98%
“…Earlier study showed that sorption of PFOS on PE, PS, and PVC decreased with increasing pH (Wang et al, 2015). Tizaoui et al (2017) also reported that increasing pH of reaction system can reduce endocrine disrupting chemicals (EDCs) adsorption on PA significantly. On the other hand, ionic strength, to a certain extent, could affect the electrostatic interactions since the electrolytes can compete with adsorbate for electrostatic sites (Shen and Gondal, 2017).…”
Section: Freshwater and Seawater Systemsmentioning
confidence: 98%
“…This research examined the role of polyamide-6 for the removal and recovery of the estrogenic endocrine disruptors estrone, 17β-estradiol, 17α-ethinylestradiol and the oxidation product 2hydroxyestradiol in water. Tizaoui et al (2017) [66] described the removal of endocrine disrupting compounds such as estrone (E1), 17β-estradiol (E2) and 17α-ethinylestradiol (EE2) and the oxidation product 2-hydroxyestradiol (2OHE2) from secondary treated wastewater in Wales (United Kingdom) using polyamide 6 as a sorbent material in their study. Results explored that PA6 is an effective sorbent material for the removal and recovery of EDCs from different water environments.…”
Section: Research Article-1mentioning
confidence: 99%
“…Given that the Fenton reaction is accelerated by light, the photo-Fenton reaction provides faster rates and potential for higher amounts of pollutant mineralisation [19]. This irradiation with UV light of the Fe 3+ ions (produced by the Fenton reaction, as shown in equation [1] in the presence of H2O2 forms Fe 2+ ions with a hydroxyl radical as shown in equation [2] [20, 21,22 ]. A continuous cycle between the Fe 2+ and Fe 3+ species is generated.…”
Section: Figure 1: Molecular Structures Of Estrogensmentioning
confidence: 99%
“…[1] Fenton Reaction [2] Photo-reduction of Fe 3+ ions [3] Oxidation of organic species RH The organic ion exchange resin, Nafion, has been tested as an immobilisation technique or carrier for the iron and is also known to catalyse a wide range of reactions [23,24]. Nafion is chemically inert and a realistic option for use in WWTPs, unlike strong homogeneous acid [24,25].…”
Section: Figure 1: Molecular Structures Of Estrogensmentioning
confidence: 99%
See 1 more Smart Citation